2014
DOI: 10.1016/j.jhazmat.2014.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of phosphogypsum waste as asphaltic bitumen modifier

Abstract: The accumulation of phosphogypsum wastes from the fertilizer industries, which remain in regulated stacks occupying considerable land resources, is causing significant environment problems worldwide. In that sense, the scientific community is being pressured to find alternative ways for their disposal. In this research, we propose a novel application for phosphogypsum wastes, as a modifier of bitumen for flexible road pavements. Viscous flow tests carried out on bitumen modified with a phosphogypsum waste and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 24 publications
0
45
0
2
Order By: Relevance
“…High levels of natural radionuclides and metals were also found in these wastes (Binnemans et al 2015). It is estimated that around five tons of this waste is generated per ton of phosphoric acid produced (Enamorado et al, 2014), which exceeds the mass of product, and 100 to 280 ×10 6 ton are produced worldwide (Cuadri et al 2014;Tayibi et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…High levels of natural radionuclides and metals were also found in these wastes (Binnemans et al 2015). It is estimated that around five tons of this waste is generated per ton of phosphoric acid produced (Enamorado et al, 2014), which exceeds the mass of product, and 100 to 280 ×10 6 ton are produced worldwide (Cuadri et al 2014;Tayibi et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Potential utilization of phosphogypsum (Fig. 14), the by-product from fertilizer industries, as a bitumen modifier for paving industry was reported by CUADRI et al [68]. It was found that when activated with small quantity of sulfuric acid (0.5 wt.%), the addition of 10 wt.% phosphogypsum leads to a notable improvement in the rheological response of resulting material at high temperatures.…”
Section: Thermal Processmentioning
confidence: 87%
“…In general, the PG is used in agriculture (for soil stabilization) and construction (preparation of materials for construction / road construction), but in insufficient quantities to absorb all PG generated. The reuse of PG, especially in construction, is based on technical, economic and ecological [40,41,42]. In the world, up to 15% of PG produced is used in construction, in general, used in the production of Portland cement [41].…”
Section: Diffraction Xrdmentioning
confidence: 99%